Hybrid Learning Media Innovation: Optimization of Interactive Digital Historical Map Application for History Education Students - Abd. Haris Nasution; Flores Tanjung; Ammar Zhafran Ryanto; Arfan Diansyah (Universitas Negeri Malang, 2025)
The development of digital technology encourages the need for innovation in history learning to be more interactive, contextual, and relevant to the needs of the 21st century generation. This study aims to develop and test the feasibility and effectiveness ofInteractive Digital History Map Application in supporting history-based learning/hybrid learning for students of the History Education study program. The research method used isResearch and Development(R&D) Borg & Gall model involving the stages of needs analysis, design, development, expert validation, limited trials, and field trials. The instruments used included expert validation sheets, student perception questionnaires, and learning outcome tests in the form of pre-tests and post-tests. The validation results showed that the application was very feasible to use, with the highest scores in the content and user interface aspects. Student perceptions were also very positive towards visual appearance, navigation, and content relevance. Quantitatively, the use of the application significantly improved student learning outcomes, with an average pre-test score of 61.23 increasing to 81.98 in the post-test and a score ofNormalized Gainof 0.53. In conclusion, this application is effective in improving the quality of history learning, strengthening students' digital literacy, and is relevant to the demands of learning in the Industrial Revolution 4.0 and Society 5.0 eras.